A method for preparing photothermal conversion hydrogel for use in low temperature environments
By electrostatically self-assembling metal ions on the surface of Ti3C2 MXene and preparing M@Ti3C2 MXene hybrids, the existing photothermal conversion hydrogels exhibit low photothermal conversion efficiency and slow response in low temperature environments are solved, and the problem of low photothermal conversion efficiency and slow response of existing photothermal conversion hydrogels is achieved. Efficient photothermal conversion and volume shrinkage effect in low-temperature environments, suitable for low-temperature photocontrol devices.
Patent Information
- Application Number
- CN202310725260.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing photothermal conversion hydrogels exhibit low photothermal conversion efficiency, slow response and difficult to apply in low temperature environments, especially the poor stability and low photothermal conversion efficiency of traditional photothermal conversion materials.
The metal ions were firmly anchored on the surface of Ti3C2 MXene by electrostatic self-assembly, and the M@Ti3C2 MXene hybrid was prepared, and a composite hydrogel was obtained by ultraviolet light polymerization. The hydrogel still had a low temperature environment of ≤0°C. Excellent photothermal conversion performance and volume shrinkage effect.
It realizes efficient photothermal conversion and volume shrinkage in low-temperature environments, exhibits full-spectrum absorption characteristics, has a good response to sunlight, and has a good ability to resist environmental heat dissipation. It is suitable for light in low-temperature environments. Control device field.
Smart Images

Figure CN116655851B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a photothermal conversion hydrogel, and in particular to a method for preparing a photothermal conversion hydrogel used in a low-temperature environment. Background Art
[0002] Photothermal conversion hydrogel is a smart hydrogel that can convert light energy into heat energy and use heat energy to drive the hydrogel's shape, volume or transmittance and other properties to undergo a large and reversible change. Due to the characteristics of light stimulation such as temporal and spatial precision, non-contact and remote control, photothermal conversion hydrogel is widely used in bionic devices, soft robots and light-controlled devices.
[0003] In the prior art, photothermal conversion hydrogels obtained by compounding photothermal conversion materials with thermal responsive hydrogels have been widely studied. For example: CN 105504150 A doped graphene oxide (GO) into poly (N-isopropylacrylamide) hydrogel, and the photothermal conversion performance of the hydrogel can be controlled by controlling the amount of GO, but GO has poor dispersibility in the hydrogel system and is prone to phase separation. Patent CN 109276538 A doped copper sulfide into gelatin hydrogel to achieve drug release control by "on" and "off" of light irradiation, but transition metal sulfides have poor stability and are easily oxidized under repeated laser irradiation conditions. Patent CN109824922 B dispersed mesoporous nanosilica loaded with indocyanine green (ICG) into a silk fibroin solution to obtain a near-infrared light-responsive hydrogel, but organic small molecule materials usually require complex chemical synthesis, and there is photobleaching under light, which seriously hinders practical applications. In addition, these traditional photothermal conversion materials have low photothermal conversion efficiency, which makes the heat generated during illumination easily dissipated by the environment, and the hydrogel is slow or even difficult to reach the volume phase transition temperature, resulting in slow response of the hydrogel, which limits the application of photothermal conversion hydrogel in various environments, especially in low temperature scenarios. x 、Au / Ti3C2T x 、Pd / Ti3C2T x The methods use olefin monomers as initiators to initiate polymerization in aqueous solution, organic solvent or polyol aqueous solution to obtain polymer organic hydrogels. However, the methods cannot achieve phase change and near-infrared response of the hydrogels, let alone photothermal conversion in a low-temperature environment. Summary of the invention
[0004] Purpose of the invention: The present invention aims to provide a method for preparing a photothermal conversion hydrogel for use in a low-temperature environment with good photothermal conversion performance and volume shrinkage effect.
[0005] Technical solution: The method for preparing the photothermal conversion hydrogel used in a low-temperature environment of the present invention comprises the following steps:
[0006] (1) stirring and mixing a metal ion precursor solution and a Ti3C2 MXene dispersion to obtain a metal ion and Ti3C2 MXene electrostatic self-assembly suspension;
[0007] (2) adding a reducing agent to the above suspension to reduce the metal ions to obtain a M@Ti3C2 MXene hybrid;
[0008] (3) Under an inert atmosphere, the M@Ti3C2 MXene hybrid, the thermosensitive monomer, the photoinitiator and the cross-linking agent are sequentially dissolved in a solvent to obtain a prepolymer solution;
[0009] (4) polymerizing the prepolymer solution through ultraviolet light to obtain a composite hydrogel;
[0010] The hydrogel prepared by the preparation method still has photothermal conversion performance and volume shrinkage effect in a low-temperature environment of ≤0°C.
[0011] Furthermore, in step (1), the metal ion precursor is one or two of palladium chloride, chloroauric acid, silver nitrate or copper sulfate.
[0012] Furthermore, in step (1), the mass ratio of the Ti3C2 MXene to the metal ion is 1:0.2-0.5, the stirring time is 0.5h-2h, and the temperature is 20-30°C.
[0013] Furthermore, in step (2), the reducing agent is hydrazine hydrate, sodium borohydride, formic acid or N,N-dimethylformamide; the mass ratio of the reducing agent to the metal ion is 1:1-2; and the reduction process adopts ultrasonic oscillation, and the ultrasonic time is 10-30 minutes.
[0014] Furthermore, in step (2), after the reduction step is completed, the product is washed and dried, the washing reagent is deionized water, ethanol or acetone, the washing number is 3 to 6 times, the drying temperature is 50 to 80° C., and the drying time is 6 to 10 hours.
[0015] Furthermore, in step (3), the inert atmosphere is one of argon, helium, and nitrogen; the thermosensitive monomer is one of N-vinyl caprolactam, N,N-diethylacrylamide, and 2-isopropyl-2-oxazoline; the photoinitiator is one of 2-hydroxy-2-methylpropiophenone, methyl benzoylformate, and benzoin dimethyl ether; and the crosslinking agent is one of N,N'-methylenebisacrylamide, divinylbenzene, and diisocyanate.
[0016] Furthermore, in step (3), the mass ratio of the thermosensitive monomer, the M@Ti3C2 MXene hybrid, the photoinitiator and the cross-linking agent is 1:0.0008:0.005:0.002 to 1:0.0056:0.01:0.006.
[0017] Furthermore, in step (4), the ultraviolet irradiation time is 2 to 5 minutes, and the ultraviolet light power density is 50 to 100 mW / cm 2 .
[0018] Principle of the invention: The present invention firmly anchors metal ions on the surface of Ti3C2 MXene through electrostatic self-assembly, and prepares the photothermal conversion material M@Ti3C2 MXene through one-step reduction. Due to the synergistic effect of the localized surface plasmon resonance characteristics of metals such as Pd, Au, Ag and Cu and the photothermal characteristics of Ti3C2 MXene, the photothermal generation rate of the composite hydrogel is higher than the ambient heat dissipation rate, thus showing excellent photothermal conversion and volume shrinkage effects.
[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The composite hydrogel prepared by the above preparation method exhibits excellent photothermal conversion and volume shrinkage effects; (2) The composite hydrogel has the characteristics of full-spectrum absorption: in addition to responding to near-infrared light, it also has good photothermal conversion and volume shrinkage effects for sunlight; (3) The composite hydrogel still maintains excellent photothermal conversion performance and volume shrinkage effect even in a low-temperature environment of ≤0°C, and exhibits good ability to resist environmental heat dissipation, which is conducive to its application in the field of light-controlled devices in low-temperature cold environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a preparation flow chart of the present invention;
[0021] Figure 2 is a transmission electron microscope image of the photothermal conversion material M@Ti3C2 MXene in Example 4;
[0022] Figure 3 It is the Fourier infrared spectrum of M@Ti3C2 MXene in Example 4 and Ti3C2 MXene in Comparative Example 2. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0024] Example 1
[0025] (1) 3.3 mL of 2 mg / mL PdCl2 precursor solution was added to 10 mL of 2 mg / mL Ti3C2 MXene nanosheet dispersion, and the resulting solution was stirred for 0.5 h at 20 °C.
[0026] (2) 800 μL of 5 mg / mL hydrazine hydrate solution was added to the mixture in step (1) and ultrasonicated for 10 min, then washed with deionized water three times, and then placed in a 50° C. oven for 6 h to obtain a Pd@Ti3C2 MXene hybrid.
[0027] (3) Under argon atmosphere, 0.8 mg Pd@Ti3C2 MXene, 1 g N-vinyl caprolactam monomer, 5 mg photoinitiator 2-hydroxy-2-methylpropiophenone, and 2 mg cross-linker N,N'-methylenebisacrylamide were dissolved in 9 mL of deionized water in sequence to obtain a prepolymer solution; the mass ratio of N-vinyl caprolactam to Pd@Ti3C2 MXene was 1:0.0008.
[0028] (4) The prepolymer solution obtained in step (3) was injected into a polytetrafluoroethylene mold and heated at 50 mW / cm2 in an ice water bath. 2 The hydrogel sample was irradiated with ultraviolet light for 2 minutes. The preparation flow chart is as follows Figure 1 shown.
[0029] Example 2
[0030] (1) 2.6 mL of 2 mg / mL HAuCl4 and 2.6 mL of 2 mg / mL AgNO3 precursor solution were added to 10 mL of 2 mg / mL Ti3C2 MXene nanosheet dispersion, and the resulting solution was stirred for 1 h at 30 °C.
[0031] (2) 1 mL of 5 mg / mL sodium borohydride solution was added to the mixture in step (1) and ultrasonicated for 15 min, then washed with ethanol 4 times, and then placed in an oven at 60 °C for 7 h to obtain Au / Ag@Ti3C2 MXene hybrid.
[0032] (3) Under a helium atmosphere, 1.6 mg Au / Ag@Ti3C2 MXene, 1 g N,N-diethylacrylamide monomer, 7 mg photoinitiator methyl benzoylformate, and 3 mg cross-linker divinylbenzene were dissolved in 9 mL of deionized water in sequence to obtain a prepolymer solution; the mass ratio of N,N-diethylacrylamide to Au / Ag@Ti3C2 MXene was 1:0.0016.
[0033] (4) The prepolymer solution obtained in step (3) was injected into a polytetrafluoroethylene mold and heated at 60 mW / cm2 in an ice water bath.2 The sample was irradiated with ultraviolet light for 3 min to obtain a hydrogel sample.
[0034] Example 3
[0035] (1) 6.3 mL of 2 mg / mL AgNO3 precursor solution was added to 10 mL of 2 mg / mL Ti3C2 MXene nanosheet dispersion, and the resulting solution was stirred for 1.5 h at 25 °C.
[0036] (2) 800 μL of 5 mg / mL formic acid solution was added to the mixture in step (1) and ultrasonicated for 20 min, then washed with acetone 5 times, and then placed in an oven at 70 °C for 8 h to obtain Ag@Ti3C2 MXene hybrid.
[0037] (3) Under nitrogen atmosphere, 4.0 mg of Ag@Ti3C2 MXene, 1 g of 2-isopropyl-2-oxazoline monomer, 10 mg of photoinitiator benzoin dimethyl ether, and 4 mg of cross-linking agent divinylbenzene were dissolved in 9 mL of deionized water in sequence to obtain a prepolymer solution; the mass ratio of 2-isopropyl-2-oxazoline to Ag@Ti3C2 MXene was 1:0.004.
[0038] (4) The prepolymer solution obtained in step (3) was injected into a polytetrafluoroethylene mold and heated at 80 mW / cm2 in an ice water bath. 2 The sample was irradiated with ultraviolet light for 4 min to obtain a hydrogel sample.
[0039] Example 4
[0040] (1) 5 mL of 2 mg / mL CuSO4 and 5 mL of 2 mg / mL PdCl2 precursor solution were added to 10 mL of 2 mg / mL Ti3C2 MXene nanosheet dispersion, and the resulting solution was stirred for 2 h at 30 °C.
[0041] (2) 1 mL of 5 mg / mL N,N-dimethylformamide solution was added to the mixture in step (1) and ultrasonicated for 30 min. The mixture was then washed with deionized water for 6 times and then placed in an oven at 80 °C for 10 h to obtain a Cu / Pd@Ti3C2 MXene hybrid. The transmission electron microscopy image is shown in FIG. Figure 2 shown.
[0042] (3) Under a nitrogen atmosphere, 5.6 mg Cu / Pd@Ti3C2 MXene, 1 g N-vinyl caprolactam monomer, 10 mg photoinitiator 2-hydroxy-2-methylpropiophenone, and 6 mg crosslinker diisocyanate were dissolved in 9 mL of deionized water to obtain a prepolymer solution; the mass ratio of N-vinyl caprolactam to Cu / Pd@Ti3C2 MXene was 1:0.0056.
[0043] (4) The prepolymer solution obtained in step (3) was injected into a polytetrafluoroethylene mold and heated to 100 mW / cm2 in an ice water bath. 2 The sample was irradiated with ultraviolet light for 5 min to obtain a hydrogel sample.
[0044] Comparative Example 1
[0045] This comparative example is a method for preparing a hydrogel without M@Ti3C2 MXene, and the steps are as follows:
[0046] (1) Under a nitrogen atmosphere, 1 g of N-vinyl caprolactam monomer, 10 mg of a photoinitiator, 2-hydroxy-2-methylpropiophenone, and 6 mg of a crosslinking agent, diisocyanate, were dissolved in 9 mL of deionized water to obtain a prepolymer solution.
[0047] (2) The prepolymer solution obtained in step (1) was injected into a polytetrafluoroethylene mold and heated to 100 mW / cm2 in an ice water bath. 2 The sample was irradiated with ultraviolet light for 5 min to obtain a hydrogel sample.
[0048] Comparative Example 2
[0049] This comparative example is a method for preparing a hydrogel containing only Ti3C2 MXene, and the steps are as follows:
[0050] (1) Under a nitrogen atmosphere, 5.6 mg of Ti3C2 MXene, 1 g of N-vinyl caprolactam monomer, 10 mg of photoinitiator 2-hydroxy-2-methylpropiophenone, and 6 mg of crosslinker diisocyanate were dissolved in 9 mL of deionized water in sequence to obtain a prepolymer solution.
[0051] (2) The prepolymer solution obtained in step (1) was injected into a polytetrafluoroethylene mold and heated to 100 mW / cm2 in an ice water bath. 2 The sample was irradiated with ultraviolet light for 5 min to obtain a hydrogel sample.
[0052] Comparative Example 3
[0053] This comparative example is a method for preparing a hydrogel of acrylamide, a non-thermosensitive monomer, and the steps are as follows:
[0054] (1) 5 mL of 2 mg / mL CuSO4 and 5 mL of 2 mg / mL PdCl2 precursor solution were added to 10 mL of 2 mg / mL Ti3C2 MXene nanosheet dispersion, and the resulting solution was stirred for 2 h at 30 °C.
[0055] (2) 1 mL of 5 mg / mL N,N-dimethylformamide solution was added to the mixture in step (1) and ultrasonicated for 30 min. The mixture was then washed with deionized water for 6 times and then placed in an oven at 80 °C for 10 h to obtain a Cu / Pd@Ti3C2 MXene hybrid.
[0056] (3) Under a nitrogen atmosphere, 5.6 mg Cu / Pd@Ti3C2 MXene, 1 g acrylamide monomer, 10 mg photoinitiator 2-hydroxy-2-methylpropiophenone, and 6 mg cross-linking agent diisocyanate were dissolved in 9 mL of deionized water in sequence to obtain a prepolymer solution; the mass ratio of acrylamide to Cu / Pd@Ti3C2 MXene was 1:0.0056.
[0057] (4) The prepolymer solution obtained in step (3) was injected into a polytetrafluoroethylene mold and heated to 100 mW / cm2 in an ice water bath. 2 The sample was irradiated with ultraviolet light for 5 min to obtain a hydrogel sample.
[0058] In order to explore the effect of the amount of M@Ti3C2 MXene on the photothermal conversion effect of the hydrogel, the hydrogel samples prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were cut into a 2.0 cm × 2.0 cm × 0.5 cm (length × width × height) cuboid. 2 ) was used to irradiate the hydrogel, and a thermal imager and a digital camera were used to record the surface temperature change and volume change of the hydrogel respectively. The test results are shown in Table 1.
[0059] Table 1-Effect of M@Ti3C2 MXene dosage on photothermal conversion and volume shrinkage of hydrogel
[0060] serial number <![CDATA[T0]]> <![CDATA[T 30 ]]> <![CDATA[T 60 ]]> <![CDATA[T 90 ]]> <![CDATA[T 120 ]]> <![CDATA[T 150 ]]> <![CDATA[T 180 ]]> <![CDATA[V 180 / V0]]> Example 1 23.0 31.9 35.6 38.2 41.2 43.8 45.8 65% Example 2 23.0 34.6 40.9 44.6 47.9 50.3 53.3 53% Example 3 23.0 38.9 48.4 53.6 56.9 60.5 63.2 46% Example 4 23.0 42.9 55.3 60.9 64.6 66.9 69.5 42% Comparative Example 1 23.0 23.9 24.6 25.4 25.7 26.3 27.1 97% Comparative Example 2 23.0 34.2 41.1 44.9 48.2 50.8 53.6 53% Comparative Example 3 23.0 40.3 52.6 58.2 63.1 65.8 67.6 99%
[0061] Note: In the table, T represents temperature in °C; V represents volume; the lower right corners of T and V represent time in seconds; V 180 / V0 represents the ratio of the volume of the hydrogel after near-infrared light irradiation for 180s to the original volume.
[0062] As can be seen from Table 1, the warming effect and volume shrinkage of the hydrogel are positively correlated with the content of M@Ti3C2 MXene in the hydrogel. The hydrogel obtained in Example 4 uses the M@Ti3C2 MXene in the matrix to quickly absorb near-infrared light energy and convert it into a large amount of heat energy. The surface temperature of the hydrogel increases from 23.0°C to 69.5°C. Compared with the initial temperature, the temperature increases by 46.5°C, and the volume shrinks to 42% of the original volume; under the same conditions, the hydrogel sample without M@Ti3C2MXene obtained in Comparative Example 1 has a temperature of 27.1°C. Compared with the initial temperature, the temperature only rises by 4.1°C, and the volume has almost no change; the hydrogel with the same content of Ti3C2 MXene obtained in Comparative Example 2 is worse than that in Example 4 in terms of photothermal conversion and volume shrinkage; although the hydrogel obtained in Comparative Example 3 also shows a good warming effect, it cannot achieve volume shrinkage because it is polymerized from non-thermosensitive monomers. The results show that the composite hydrogel has excellent photothermal conversion and volume shrinkage properties.
[0063] In order to explore the photothermal conversion ability of the composite hydrogel for light in other wavelength ranges (such as sunlight) except near-infrared light, the hydrogels prepared in Example 4 and Comparative Example 1 were subjected to a xenon lamp irradiation temperature rise test. The test process is as follows: the two groups of samples were placed under a power of 1.5 W / cm 2 The hydrogel was irradiated under a xenon lamp, and the surface temperature change and volume change of the hydrogel were recorded using a thermal imager and a digital camera, respectively. The test results are shown in Table 2.
[0064] Table 2-Photothermal conversion and volume shrinkage effect of hydrogel under xenon lamp irradiation
[0065] serial number <![CDATA[T0]]> <![CDATA[T1]]> <![CDATA[T2]]> <![CDATA[T3]]> <![CDATA[T4]]> <![CDATA[T5]]> <![CDATA[V5 / V0]]> Comparative Example 1 23.0 24.2 25.0 25.5 25.8 25.9 99% Example 4 23.0 31.2 36.3 38.9 40.6 41.7 70%
[0066] Note: In the table, T represents temperature in °C; V represents volume; the lower right subscripts of T and V represent time in min; V5 / V0 represents the ratio of the volume of the hydrogel after 5 min of xenon light irradiation to the original volume.
[0067] As shown in Table 2, the sample prepared in Example 4 with a M@Ti3C2 MXene content of 0.056wt.% rises in temperature by 18.7°C after 5 minutes of xenon lamp irradiation, and its volume shrinks to 70% of its original volume; the sample prepared in Comparative Example 1 without M@Ti3C2 MXene rises in temperature by 2.9°C under the same conditions, and its volume remains almost unchanged. The experimental results show that the prepared hydrogel containing M@Ti3C2MXene also has good responsiveness to sunlight.
[0068] In order to study the photothermal conversion ability of the hydrogel under low temperature environment, the hydrogel prepared in Example 4 was placed in an environment of different temperatures and subjected to near-infrared laser (808 nm, 1.0 W / cm 2 ) irradiation, and the surface temperature change process and volume change rate of the hydrogel were recorded using a thermal imager and a digital camera respectively. The test results are shown in Table 3.
[0069] Table 3-Photothermal conversion and volume shrinkage effect of hydrogels in low temperature environment
[0070] serial number Ambient temperature <![CDATA[T0]]> <![CDATA[T 30 ]]> <![CDATA[T 60 ]]> <![CDATA[T 90 ]]> <![CDATA[T 120 ]]> <![CDATA[T 150 ]]> <![CDATA[T 180 ]]> <![CDATA[V 180 / V0]]> Example 4 -5℃ 23.0 32.9 37.1 38.5 39.6 40.7 41.2 70% Example 4 0℃ 23.0 35.3 39.9 41.7 43.3 44.5 45.2 66% Comparative Example 2 -5℃ 23.0 24.1 24.6 24.9 25.3 25.7 26.1 99% Comparative Example 2 0℃ 23.0 24.9 26.1 26.9 27.6 28.1 28.5 97%
[0071] Note: In the table, T represents temperature in °C; V represents volume; the lower right corners of T and V represent time in seconds; V 180 / V0 represents the ratio of the volume of the hydrogel after 180s of near-infrared light irradiation to the original volume.
[0072] It can be seen from Table 3 that the hydrogel containing M@Ti3C2 MXene still has good photothermal conversion and volume shrinkage properties at low temperatures. For example, in an environment of 0°C, after 180s of near-infrared laser irradiation, the temperature rises by about 22.2°C, and the volume can shrink to 66% of the original volume, which is not much different from the experimental results at room temperature of 25°C; the Ti3C2MXene hydrogel with the same content prepared in Comparative Example 2 has not reached the phase transition temperature (32°C) after 180s of near-infrared laser irradiation in an environment of 0°C, and the volume does not show obvious shrinkage, which is very different from the results at room temperature of 25°C. This result shows that the prepared hydrogel containing M@Ti3C2 MXene has a good ability to resist heat dissipation in low-temperature environments and can be used in low-temperature environments. The Fourier infrared spectra of M@Ti3C2 MXene in Example 4 and Ti3C2MXene in Comparative Example 2 are shown in the figure. Figure 3 shown.
Claims
1. A method for preparing a photothermal conversion hydrogel for use in a low temperature environment, characterized in that: The steps include: (1) stirring and mixing the metal ion precursor solution and the Ti3C2MXene dispersion to obtain a metal ion and Ti3C2MXene electrostatic self-assembly suspension; (2) adding a reducing agent to the above suspension to reduce the metal ions to obtain a M@Ti3C2 MXene hybrid; (3) Under an inert atmosphere, the M@Ti3C2 MXene hybrid, the thermosensitive monomer, the photoinitiator and the cross-linking agent are sequentially dissolved in a solvent to obtain a prepolymer solution; (4) The prepolymer solution is polymerized by ultraviolet light to obtain a composite hydrogel; The hydrogel prepared by the preparation method still has photothermal conversion performance and volume shrinkage effect in a low temperature environment of ≤0°C; in step (1), the metal ion precursor is one or two of palladium chloride, chloroauric acid, silver nitrate or copper sulfate; in step (3), the thermosensitive monomer is one of N-vinyl caprolactam, N,N-diethylacrylamide, and 2-isopropyl-2-oxazoline.
2. The method for preparing a photothermal conversion hydrogel for use in a low temperature environment according to claim 1, characterized in that: In step (1), the mass ratio of the Ti3C2 MXene to the metal ions is 1:0.2-0.
5.
3. The method for preparing a photothermal conversion hydrogel for use in a low temperature environment according to claim 1, characterized in that: In step (1), the stirring time is 0.5 h to 2 h, and the temperature is 20 to 30 °C.
4. The method for preparing a photothermal conversion hydrogel for use in a low temperature environment according to claim 1, characterized in that: In step (2), the reducing agent is hydrazine hydrate, sodium borohydride, formic acid or N,N-dimethylformamide.
5. The method for preparing a photothermal conversion hydrogel for use in a low temperature environment according to claim 1, characterized in that: In step (2), the mass ratio of the reducing agent to the metal ion is 1:1-2.
6. The method for preparing a photothermal conversion hydrogel for use in a low temperature environment according to claim 1, characterized in that: In step (2), after the reduction step is completed, the product is washed and dried, the washing reagent is deionized water, ethanol or acetone, the washing number is 3 to 6 times, the drying temperature is 50 to 80 ° C, and the drying time is 6 to 10 hours.
7. The method for preparing a photothermal conversion hydrogel for use in a low temperature environment according to claim 1, characterized in that: In step (3), the inert atmosphere is one of argon, helium, and nitrogen; the photoinitiator is one of 2-hydroxy-2-methylpropiophenone, methyl benzoylformate, and benzoin dimethyl ether; and the crosslinking agent is one of N,N'-methylenebisacrylamide, divinylbenzene, and diisocyanate.
8. The method for preparing a photothermal conversion hydrogel for use in a low temperature environment according to claim 1, characterized in that: In step (3), the mass ratio of the thermosensitive monomer, the M@Ti3C2 MXene hybrid, the photoinitiator and the cross-linking agent is 1:0.0008:0.005:0.002 to 1:0.0056:0.01:0.
006.
9. The method for preparing a photothermal conversion hydrogel for use in a low temperature environment according to claim 1, characterized in that: In step (4), the irradiation time of the ultraviolet light is 2 to 5 min, and the power density of the ultraviolet light is 50 to 100 mW / cm 2 .
Citation Information
Patent Citations
Preparation method of poly(N-isopropyl acrylamide) / oxidized graphene hydrogel
CN105504150A
Design and synthesis method of medicine-carrying hydrogel realizing optothermal response
CN109276538A
A hydrogel material with infrared light response and its preparation method
CN109824922B
A method for preparing organic hydrogels via Ag / MXene-initiated free radical polymerization
CN112876585B
Ag / MXene-initiated free radical polymerization and organic hydrogel preparation method
CN112876585A